2023
DOI: 10.1186/s12944-023-01775-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of liver fat content with systemic metabolism and chronic complications in patients with type 2 diabetes mellitus

Abstract: Objective This study investigated the correlation of liver fat content (LFC) with metabolic characteristics and its association with chronic complications in type 2 diabetes mellitus (T2DM) patients. Methods Eighty-one prospectively enrolled T2DM patients were divided into non-alcoholic fatty liver disease (NAFLD) group and the non-NAFLD group according to the presence of NAFL complications. LFC was determined by MRI IDEAL-IQ Sequence, and patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Hyperglycemia is one of the most important factors related to diabetic complication [ 28 , 29 ]. Diabetes duration is known to be one risk factor for DPN in T2DM individuals [ 30 ]. In this research, we observed increased levels of HbA1c in T2DM participants with peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia is one of the most important factors related to diabetic complication [ 28 , 29 ]. Diabetes duration is known to be one risk factor for DPN in T2DM individuals [ 30 ]. In this research, we observed increased levels of HbA1c in T2DM participants with peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…LFC showed a significant correlation with the severity of metabolic disturbances in patients with T2DM and was identified as a risk factor for atherosclerotic cardiovascular disease. An increase in LFC puts diabetic patients at higher risk for metabolic disturbances and chronic complications, which demonstrates the importance of accurate steatosis grading and early therapeutic interventions [143].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Of those, 20 were carried out in Asia [18,20−23,26,28,30,35,37−40,44−50], 14 in Europe [11,12,19,24,25,29,31−34,36,41−43] and 2 in America [13,27]. A total of 30 were reported as cross-sectional [11−13,19,20,22−34,37−39,41−44,46−50], 4 as case-control [18,35,36,45] and 2 as cohort studies [21,40]. A total of 32 were performed on patients with DM [11,12,18 [11,12,[42][43][44]49] and 2 reported on a mixed diabetic population [25,40], while in 1 article, the type of diabetes was not clarified [37].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Of those, 20 were carried out in Asia [18,[20][21][22][23]26,28,30,35,[37][38][39][40][44][45][46][47][48][49][50], 14 in Europe [11,12,19,24,25,29,[31][32][33][34]36,[41][42][43] and 2 in America [13,27]. A total of 30 were reported as cross-sectional [11][12][13]19,20,[22][23][24][25][26][27][28][29][30][31][32]…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation